Prevalence of Rheumatic Heart Disease in Iran: A Systematic Review and Meta-analysis - Zainab Qazizadeh; Leila Shahmoradi; Mahmood Moosazadeh; Leila Shahbaznejad; Mohammad Sadegh Rezai (Mazandaran University of Medical Sciences, 2021)
Context: Rheumatic Heart Disease (RHD) remains the prominent cause of morbidity and mortality among young individuals in developing countries. The present research aimed to estimate the prevalence of RHD in Iran.  Data Sources: In this review, all population-based studies with a sample size of ≥500 participants related to the prevalence of RHD were included. The search was conducted in national and international databases. The combination of medical subject headings and free-term text items concerning the incidence, prevalence, rheumatic fever, RHD, and Iran were used in this study.  Data Extraction: In this systematic review, 490 papers were identified. A total of 296 articles were screened; of which, 9 qualified articles were selected for the final data analysis. All studies were of cross-sectional, and descriptive natures. Two authors used the data extraction form to independently extract relevant data from the included studies. Disagreements between the authors were reconciled through discussion and consensus. Results: The overall prevalence of RHD was calculated as 0.02% (20/100000 population). This prevalence rate is estimated based on studies conducted in the northern, southern, eastern, western, and central regions of the country; therefore it could be an estimation of the relevant prevalence rate in Iran. However, there were no updated and high-quality data in this regard. Thus, the reported rate might be underestimated.  Conclusions: There is a need for a nationwide survey to investigate the precise prevalence of RHD in Iran. This can be achieved by creating a national database of RHD.